Widespread Occurrence of Two Carbon Fixation Pathways in Tubeworm Endosymbionts: Lessons from Hydrothermal Vent Associated Tubeworms from the Mediterranean Sea - Thiel, Vera; Hügler, Michael; Blümel, Martina; Baumann, Heike I.; Gärtner, Andrea; Schmaljohann, Rolf; Strauss, Harald; Garbe-Schönberg, Dieter; Petersen, Sven; Cowart, Dominique A.; Fisher, Charles R.; Imhoff, Johannes F. (Frontiers in Microbiology, 2012)
Vestimentiferan tubeworms (siboglinid polychetes) of the genus Lamellibrachia are common members of cold seep faunal communities and have also been found at sedimented hydrothermal vent sites in the Pacific. As they lack a digestive system, they are nourished by chemoautotrophic bacterial endosymbionts growing in a specialized tissue called the trophosome. Here we present the results of investigations of tubeworms and endosymbionts from a shallow hydrothermal vent field in the Western Mediterranean Sea. The tubeworms, which are the first reported vent-associated tubeworms outside the Pacific, are identified as Lamellibrachia anaximandri using mitochondrial ribosomal and cytochrome oxidase I (COI) gene sequences. They harbor a single gammaproteobacterial endosymbiont. Carbon isotopic data, as well as the analysis of genes involved in carbon and sulfur metabolism indicate a sulfide-oxidizing chemoautotrophic endosymbiont. The detection of a hydrogenase gene fragment suggests the potential for hydrogen oxidation as alternative energy source. Surprisingly, the endosymbiont harbors genes for two different carbon fixation pathways, the Calvin-Benson-Bassham (CBB) cycle as well as the reductive tricarboxylic acid (rTCA) cycle, as has been reported for the endosymbiont of the vent tubeworm Riftia pachyptila. In addition to RubisCO genes we detected ATP citrate lyase (ACL – the key enzyme of the rTCA cycle) type II gene sequences using newly designed primer sets. Comparative investigations with additional tubeworm species (Lamellibrachia luymesi, Lamellibrachia sp. 1, Lamellibrachia sp. 2, Escarpia laminata, Seepiophila jonesi) from multiple cold seep sites in the Gulf of Mexico revealed the presence of acl genes in these species as well. Thus, our study suggests that the presence of two different carbon fixation pathways, the CBB cycle and the rTCA cycle, is not restricted to the Riftia endosymbiont, but rather might be common in vestimentiferan tubeworm endosymbionts, regardless of the habitat.